SHINJU (BUNUH DIRI BERSAMA) DALAM CERPEN SONEZAKI SHINJU KARYA CHIKAMATSU MONZAEMON - Eva Amalijah (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
Abstract. This study discusses a lover suicide, shinju, in a short story entitled Sonezaki Shinju written by Chikamatsu Monzaemon. Shinju Sonezaki tells the marriage customs in Japanese society done by matchmaking (miai kekkon). However, the match failed to take place because the figures were refused an arranged marriage and do shinju with his girlfriend. By utilizing the approach of sociology of literature, this study discovered three things, namely shinju as a form of resistance against Japanese tradition; shinju as a way out of giri and ninjo conflict; Shinju as a representation of Shinto belief